2017
DOI: 10.3310/hsdr05030
|View full text |Cite
|
Sign up to set email alerts
|

Researching outcomes from forensic services for people with intellectual or developmental disabilities: a systematic review, evidence synthesis and expert and patient/carer consultation

Abstract: BackgroundInpatient services for people with intellectual and other types of developmental disabilities (IDD) who also have forensic or risk issues are largely provided in secure hospitals. Although this is a health service sector with high levels of expenditure, there is limited empirical information on patient outcomes from such services. In order for a future substantive longitudinal outcomes study in forensic IDD services to be informed and feasible, more needs to be understood about the outcome domains th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 67 publications
0
20
0
Order By: Relevance
“…This has addressed observed methodological issues with previously published treatment outcome studies, many of which were single service, and report patients' LoS in relation to their stay within that service only. 2 , 25 This is problematic, as unit moves are common within the long-stay group, with patients having an average of 1.43 unit changes in their pathway, with 31% having been in two settings, 23% in three settings and 18% in four or more settings within their continuous care pathway. 1 The difference between these two figures for both the intellectual disability and non-intellectual disability groups was considerable, at a median of 5.92 and 8.33 years, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…This has addressed observed methodological issues with previously published treatment outcome studies, many of which were single service, and report patients' LoS in relation to their stay within that service only. 2 , 25 This is problematic, as unit moves are common within the long-stay group, with patients having an average of 1.43 unit changes in their pathway, with 31% having been in two settings, 23% in three settings and 18% in four or more settings within their continuous care pathway. 1 The difference between these two figures for both the intellectual disability and non-intellectual disability groups was considerable, at a median of 5.92 and 8.33 years, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The researchers selected and briefed the panel of experts. Little literature is available regarding the number of experts needed for a Delphi expert panel (Shelton & Creghan ), but 15–20 experts seem to be standard based on a review of published Delphi studies (Morrissey et al ). Purposive sampling was used in the recruitment of panel experts.…”
Section: Methodsmentioning
confidence: 99%
“…32 The Code of Practice 26 recommends that people with IDD have the right to have an appropriate adult in attendance at the police interview, programmes designed to rehabilitate, 11,12 and assessed how to best evaluate treatment outcomes. 13,14 Nevertheless, people with IDD remain a vulnerable group. In 2009, the Bradley Report, which focused on people with mental health problems or IDD in the CJS was published.…”
Section: Policementioning
confidence: 99%
“…In the majority of cases, discharge is prompted by the care programme approach process, and linked to the everyday improvement and recovery of patients, as well as the availability of suitable community supervision, or placement options. 13,14 A number of studies have evaluated the outcomes of patients within inpatient secure IDD services. One study reported that of 138 patients treated over a 6-year period, 77 were discharged and 61 were current inpatients.…”
Section: Inpatient Secure Idd Servicesmentioning
confidence: 99%
See 1 more Smart Citation